The mental health complications of abortion - Miller, Calum (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
Mental health is the most commonly cited reason for abortion in many countries. Pro-abortion advocates argue that legally protecting the unborn imposes an unbearable toll on mothers' mental health, exposing them to stress and conditions such as depression. The chapter examines whether this is supported by evidence. The chapter analyses two major reviews, by the National Collaborating Centre for Mental Health (2011) and Fergusson (2013), neither authored by pro-life researchers, and answers objections to a link between abortion and worse mental health. Evidence shows associations between abortion and increased risks of suicide, anxiety, and likely substance abuse, persisting after adjusting for prior mental health; the most reliable study attributed 1.5-5.5% of disorders to abortion. The claim that abortion preserves mental health thus has no evidentiary basis; a compassionate response to unplanned pregnancy is to support continuing it rather than exposing mothers to abortion's risks.